Memória esportiva do futebol sergipano por Viana Filho - Nunes, Vitor Gabriel Gonçalves (2024)
This research has as its motto the study of the sporting memory of football in Sergipe from the perspective of Francisco Viana Filho. Born in Aracaju, on eleven days in 1934, Viana Filho became one of the biggest names in sports chronicle, bequeathing a wellfounded and rich work of historical memory of Sergipe sport. Taking as a theoretical contribution the concept of Norbert Elias and Eric Dunning, as well as collective memory coined by the French intellectual Maurice Halbwachs, the aim is to not only carry out a historical analysis on the subject, but also contribute to studies of the history of football in Sergipe.